2015
DOI: 10.1007/s00232-015-9811-z
|View full text |Cite
|
Sign up to set email alerts
|

TargetFreeze: Identifying Antifreeze Proteins via a Combination of Weights using Sequence Evolutionary Information and Pseudo Amino Acid Composition

Abstract: Antifreeze proteins (AFPs) are indispensable for living organisms to survive in an extremely cold environment and have a variety of potential biotechnological applications. The accurate prediction of antifreeze proteins has become an important issue and is urgently needed. Although considerable progress has been made, AFP prediction is still a challenging problem due to the diversity of species. In this study, we proposed a new sequence-based AFP predictor, called TargetFreeze. TargetFreeze utilizes an enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Amino acid sequences of the four wheat proteins were analyzed using TargetFreeze, a recently‐developed bioinformatics tool that predicts the likelihood of a protein to possess antifreeze activity . This would be suggested if the score obtained is higher than the threshold of 0.66.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amino acid sequences of the four wheat proteins were analyzed using TargetFreeze, a recently‐developed bioinformatics tool that predicts the likelihood of a protein to possess antifreeze activity . This would be suggested if the score obtained is higher than the threshold of 0.66.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid sequences of the four wheat proteins were analyzed using TargetFreeze, a recentlydeveloped bioinformatics tool that predicts the likelihood of a protein to possess antifreeze activity. 24 This would be suggested if the score obtained is higher than the threshold of 0.66. Values of 0.115 and 0.017 were obtained for TaBAS1 (BAA19099.1) and TaENO (AGH20061.1), respectively, indicating that these two proteins are not predicted to affect ice formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advancements of genome sequencing, a large number of sequenced proteins have been accumulated and need to be functionally annotated. Many auto-annotation tools exist to identify antifreeze proteins, such as TargetFreeze (He et al, 2015), AFP_PSSM (Zhao et al, 2012), CryoProtect (Pratiwi et al, 2017), and afpCOOL (Eslami et al, 2018). However, these tools use too many features ( Table 2), which may often be redundant and lead to overfitting.…”
Section: Comparison Of Our Seven Key Featuresmentioning
confidence: 99%
“…In contrast, despite the presumed convergent evolution of antifreeze proteins, Zhao et al (2012) built a classifier with high performance solely based on evolutionary features derived from position-specific scoring matrices (PSSMs), suggesting that evolutionary information is also important for identifying antifreeze proteins. He et al (2015) further compared the performances of evolutionary features with two amino acid composition metrics (i.e., amino acid composition and pseudo amino acid composition), and showed that features derived from PSSMs achieved higher performance. Similarly, Yang et al (2015) reported that among various features pertinent to identifying antifreeze proteins, features derived from PSSMs accounted for the largest proportion, though another study showed that physicochemical properties were more important (Eslami et al, 2018).…”
Section: Introductionmentioning
confidence: 99%